Performance evaluation of Gallium-68 radiopharmaceuticals production using liquid target PETtrace 800 cyclotron - Ashhar, Zarif; Ahmad Fadzil, Muhammad Fakhrurazi; Md Safee, Zaitulhusna; Aziz, Firdaus; Ibarhim, Ummi Habibah; Nik Afinde, Nik Muhammad Fitri; Mat Ail, Noratikah; Jamal Harizan, Muhammad Ali Hazizi; Halib, Dzulieza; Alek Amran, Arieffuddin; Adawiyah, Rabiatul; Abd Hamid, Mohd Hamdi Noor; et al. (Elsevier, 2024)
Due to increased demand, cyclotron has an expanding role in producing Gallium-68 (68Ga) radiopharmaceuticals using solid and liquid targets. Though the liquid target produces lower end-of-bombardment activity compared to the solid target, our study presents the performance of 68Ga radiopharmaceuticals production using the liquid target by evaluating the end-of-bombardment activity and the end-of-purification activity of 68GaGaCl3. We also present the effect of increasing irradiation time, which significantly improves the end-of-synthesis yield. From the result obtained, the end-of-bombardment activity produced was 4.48 GBq, and the 68GaGaCl3 end-of-purification activity produced was 2.51 GBq with below-limit metallic impurities. Increasing the irradiation time showed a significant increase in the end-of-synthesis activity from 1.33 GBq to 1.95 GBq for 68GaGa-PSMA-11 and from 1.13 GBq to 1.74 GBq for 68GaGa-DOTA-TATE. Based on the improvements made, the liquid target production of 68Ga radiopharmaceuticals is feasible and reproducible to accommodate up to 5 patients per production. In addition, this work also discusses the issues encountered, together with the possible corrective and preventative measures. © 2023 Elsevier Ltd